DESCEMETOCELE EM UM CANINO - RELATO DE CASO - Kommers, Luiza; Bernicker, Emanuelli Tres; Lorenset, Jéssica Andressa; Teichmann, Cristiane Elise (Salão do Conhecimento, 2017)
Relato Supervisionado da disciplina de Estágio Clínico 1 em Medicina Veterinária da UNIJUÍ